SELECTION OF GAMMA-AMINOBUTYRIC ACID PRODUCING LACTOBACILLUS AND BIFIDOBACTERIUM SYMBIONT STRAINS AS POTENTIAL PSYCHOBIOTICS - R A Yunes; E U Poluektova; M S Dyachkova; Y E Kozlovski; V S Orlova; V N Danilenko (RUDN Journal of Ecology and Life Safety, 2016)
Gamma-amino butyric acid (GABA) is an active biogenic substance, synthesized in the organisms of plants, fungi, vertebrate animals and bacteria. GABA is used in food and drugs exhibiting antihypertensive, analgesic and antidepressant properties. GABA-producing strains can be considered as delivery vehicles of GABA to specific sites of the gut. Such strains are potential antidepressants promoting adaptation in the extreme north. Lactic acid bacteria (LAB) are considered the main producers of GABA among bacteria. GABA-producing Lactobacilli are isolated from food products such as cheese, yogurt, sourdough etc. and are the source of bioactive properties assigned to those foods. The ability of Human-derived Lactobacilli and Bifidobacteria to synthesize GABA remains poorly characterized. In this paper, we screened our collection of 114 Human-derived Lactobacillus and Bifidobacterium strains for their ability to produce GABA from its precursor monosodium glutamate (MSG). As a result 58 strains belonging to the species L.plantarum , L.brevis , B.adolescentis , B.angulatum , B.dentium were able to produce GABA. The most efficient GABA-producers were Bificobacterium strains (up to 6 g/L). We selected a GABA-producing strains that was further tested in Sprague-Dawley rats. Ingestion of L.plantarum 90sk strain increased GABA in the rats’ blood and decreased the rate of stress hormone prolactin.